What explains the spread between the euro overnight rate and the ECB's policy rate? - Tobias Linzert; Sandra Schmidt (European Central Bank (ECB), 2008)
We employ a time series econometric framework to explore the structural determinants of the spread between the European Overnight Rate and the ECB's Policy Rate (EONIA spread) aiming to explain the widening of the EONIA spread from mid-2004 to mid-2006. In particular, we estimate a model on the EONIA spread since the introduction of the new operational framework in March 2004 until August 2006. We show that the increase in the EONIA spread can for the largest part be explained by the current liquidity deficit. Moreover, tight liquidity conditions as well as an increase in banks' liquidity uncertainty lead to a significant upward pressure on the spread. The ECB's liquidity policy only reduces the spread if a loose policy is conducted during the last week of a maintenance period. Interestingly, interest rate expectations have not been found to have an important influence.
Keywords: E43; E52; C22; 330; Interest Rate Determination; monetary policy implementation; operational framework; Overnight Market Rate (EONIA); Zinsstruktur; Geldmarkt; Zinspolitik; Bankenliquidität; EU-Staaten